2014
DOI: 10.1007/s00432-014-1857-2
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase polymorphisms: influence on incidence of hepatic sinusoidal obstruction syndrome in children undergoing allogeneic hematopoietic stem cell transplantation

Abstract: HPSE polymorphisms turned out to be significant independent risk factors (P = 0.030) for development of SOS and should be evaluated in further trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…59,119 In addition, a 2014 expert consensus statement recommended the investigation of defibrotide for its potential to improve outcomes of transplant-associated thrombotic microangiopathy. 120 A retrospective, multicenter survey of pediatric patients (n 5 22) reported by EBMT working parties and compared with adult patients (n 5 17) from a single center, also found that defibrotide treatment resulted in resolution of transplant-associated thrombotic microangiopathy ($ 2 schistocytes/high-power microscopic field, serum lactate dehydrogenase increase, thrombocytopenia, anemia with negative direct Coombs test, decreased haptoglobin, and no coagulopathy) following HSCT in 77% of treated patients (17/22 pediatric; 13/17 adult).…”
mentioning
confidence: 99%
“…59,119 In addition, a 2014 expert consensus statement recommended the investigation of defibrotide for its potential to improve outcomes of transplant-associated thrombotic microangiopathy. 120 A retrospective, multicenter survey of pediatric patients (n 5 22) reported by EBMT working parties and compared with adult patients (n 5 17) from a single center, also found that defibrotide treatment resulted in resolution of transplant-associated thrombotic microangiopathy ($ 2 schistocytes/high-power microscopic field, serum lactate dehydrogenase increase, thrombocytopenia, anemia with negative direct Coombs test, decreased haptoglobin, and no coagulopathy) following HSCT in 77% of treated patients (17/22 pediatric; 13/17 adult).…”
mentioning
confidence: 99%
“… 26 The development of reduced intensity conditioning allowed us to perform allo-HSCT in patients with co-morbidities who would otherwise be ineligible for this procedure, but this led to an increase in the number of patients presenting risk factors, such as metabolic syndrome and, particularly, obesity. Genetic polymorphism (GSTM1 and GSMTT1, 27 heparanase in children 28 ), deficit in antithrombine III 29 or tissue plasminogen activator 30 and resistance to the activated C protein 29 are associated with increased risk of SOS/VOD. In the pediatric setting, higher incidence of SOS/VOD is seen in the primary hemophagocytic lymphohistiocytosis, adrenoleucodystrophy osteopetrosis or thalassemia major, auto-HSCT in patients with neuroblastoma, younger age (under 1–2 years of age) and low weight.…”
Section: Risk Factorsmentioning
confidence: 99%
“…has received honoraria and research funding from Jazz Pharmaceuticals. Broad-spectrum/multiple mechanism Panel of changes in tumorogenicity-2, angiopoieten-2, L-ficolin, hyaluronic acid, and VCAM-1 [68] # L-ficolin plasma level [83] Genetic polymorphisms MTHFR C677T/A1298C [84] Heparanase single nucleotide polymorphisms [85] Hematologic and endothelial # Protein C levels [86][87][88] # Antithrombin III levels [13,87] # Type III procollagen and tPA [88] " PAI-1 antigen levels [13,[65][66][67] " Extra-cellular endothelial vesicles CD144 + [13] " vWF, thrombomodulin, soluble IAM-1* [89] Hepatic/splenic " Maximum total serum bilirubin/bilirubin increase at any point in time [90] " Total bilirubin, D-dimer [67] " Hepatocyte growth factors/with/without IL-6 [91] " APRI [70] " Splenic volume [71] " Panel of liver fibrosis indices: API, APRI, PSR, FIB-4 y [69] Inflammatory/immune response " IL-6, IL-10, TNF-a plasma levels z [92] " IL-6 plasma level at + day 7 post-HSCT [93] # IGF and IGFBP-3 plasma levels [94] API indicates age-platelet index; APRI, aspartate aminotransferase-to-platelet ratio; FIB-4, fibrosis-4; IAM, intercellular adhesion molecule; IGF, insulin-like growth factor; IGFBP, insulin-like growth factor binding protein; PAI, plasminogen [84] activator inhibitor; PSR, platelet-to-spleen ratio; tPA, tissue plasminogen activator; vWF, von Willebrand factor; VCAM, vascular cell adhesion molecule. * In patients receiving sirolimus.…”
Section: Acknowledgmentsmentioning
confidence: 99%